Pharmacovigilance: profile and notifications of the adverse drug reaction in a teaching hospital - Kattlyn Laryssa CANDIDO; Simone Von GROLL; Luciane Fátima CALDEIRA; Andreia Cristina SANCHES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: To identify the profile of adverse drug reactions (ADRs) in a tertiary public teaching hospital after the inclusion of active search, through screeners, in the pharmacovigilance service, as well from inform managers about the epidemiological data of ADRs. Method: Observational, descriptive, and exploratory study conducted in a tertiary teaching hospital in western Paraná, between July and December 2018. The search was performed by consulting the Microsoft Office Excel® program database of the Pharmacovigilance Service and the Quality and Patient Safety Sector (SQSP). It identified the profile of adverse drug reactions and notifications to the pharmacovigilance service regarding the system of spontaneous notification and tracers by active search, as well as made a brief survey of costs related to the topic. Results: In the period studied 536 notifications were reported, 74 of these were considered adverse reactions. The hospital team that reported most frequently was the nursing staff. The screeners related to antiallergic and antidotes to anticoagulants were the most sensitive with a positive predictive value of 9 and 3%, respectively. The Emergency Room (ER) was the ward with the highest number of notifications (215), mainly due to the use of the screeners. The drugs with the highest prevalence were morphine (17%) and dipyrone (10%). The exclusive cost of the reactions was R$ 1,097.56. Conclusion: The conclusion is that this study allowed the characterization of the main ADR tracers after the inclusion of active search and that in-hospital actions are needed to avoid underreporting in order to ensure efficacy and therapeutic safety.